'You must keep going' – Musculoskeletal system stress indicators of prehistoric mobile pastoralists in Western China. (16th June 2016) - Gresky, Julia; Wagner, Mayke; Schmidt-Schultz, Tyede Helen; Schwarz, Laura; Wu, Xinhua; Aisha, Ailijiang; Tarasov, Pavel E.; Schultz, Michael
Abstract: In total 110 skeletons recovered from the Late Bronze Age (ca. 1100/900–760/500 cal. BC) cemetery Liushui, Autonomous Region Xinjiang, China (36°14′41.9″N, 81°43′23″E, ca. 2850 m a.s.l.) were suitable for observation of entheseal changes (EC presence which does not involve inferring soft tissue changes) and stress fractures. Four fibrocartilaginous entheses (lateral and medial epicondyles, the attachment sites of the quadriceps muscle at the patella and the patellar ligament, and the Achilles' tendon at the calcaneus) and one fibrous enthesis (plantar aponeurosis at the calcaneus) were scored in skeletons with respective anatomical structures preserved. Some variations in EC percentage values in relation to sex and age are documented, though the relatively small sample size limits robustness of statistical interpretation. Our results do not fully support age-related EC increase. Only medial epicondylosis and lower calcaneal spur show the most frequent occurrence in the 56–70 years age group, with substantially higher scores compared to the other age groups. Both tendinitis patellae and dorsal calcaneal spur have their highest scores in the 15–23 years age group. Dorsal spur, tendinitis patellae and lateral epicondylosis are substantially higher among the female individuals than in the male skeletal remains from Liushui. Being compared with European prehistoric and industrial populations and with Californian historic hunter–gatherers, the EC prevalence of the Liushui population indicates high physical activity levels with serious injury hazard. Grave goods and absolute chronology identify the Liushui population as mobile pastoralists at an early stage of the emergence of complex mounted pastoralism as a new economic and social system in Central Asia. The chronic nature of EC in the Liushui population, particularly noticeable in the female skeletons, may suggest an insufficient time for adaptation to permanent mechanical stress unavoidable in the prevalent mountainous environments. Relatively small sample size and the multifactorial etiology of EC require cautious evaluation of the obtained results. However, given the scarcity of palaeopathological records from the study region, our reconstructions and interpretations from the high-mountain Liushui site can be offered as a frame for further testing.